Optimization of self-fermented period of waste coconut endosperm destined to feed black soldier fly larvae in enhancing the lipid and protein yields - Mohd-Noor, S.-N. (Elsevier Ltd, 2017)
The prime objective of this study was to simultaneously enhance the lipid and protein yields from black soldier fly larvae (BSFL) fed with waste coconut endosperm. The waste coconut endosperm impoverished with nutrient content lost during milk extraction was nutritively fortified via self-fermentation process with time period ranging from 2 to 8 weeks before administering to BSFL. The results showed peak nutrient content was attained from week-4 self-fermented waste coconut endosperm. Using this feed medium, the BSFL prepupae could accumulate 58 of its biomass weight with lipid. The low polyunsaturated fatty acid (6) and high C18:1 (50) also guaranteed high biodiesel quality derived from BSFL. Nevertheless, the longer BSFL rearing duration when fed with week-6 self-fermented waste coconut endosperm had triggered a slight increase in protein yield (18) in comparison with week-4 medium (15). In considering of organic waste treatment advantage of week-4 self-fermented waste coconut endosperm, a total waste reduction of 0.019 g/d was successfully measured using only 20 BSFL. Therefore, week-4 self-fermented period was concluded as an optimum to produce ideal waste coconut endosperm feed medium for BSFL in enhancing the simultaneous lipid and protein yields. © 2017 Elsevier Ltd